The a to Z of Homosexuality - Pickett, Brent L. (Rowman & Littlefield Publishers, 2009)
The history of sexuality is central to social history, the history of ideas, the realization or repression of human rights, and other areas of focus. This is also true about those who have had, or do have, what could be called minority sexualities. Same-sex attraction has generally been a minority sexuality; it has been the object of tremendous repression and vociferous complaint but also one of praise by talented poets and philosophers. The A to Z of Homosexuality provides a comprehensive survey of same-sex relations from ancient China and Greece to the contemporary world. It covers the gay rights movement from its origins in 19th century Europe to the nascent global network today. Philosophic treatments, such as natural law and queer theory, along with legal issues and court decisions are included. Global in its coverage of the variety of same-sex relations, their legal treatment, and social norms concerning same-sex attraction, this reference includes a chronology, an introductory essay, a bibliography, and cross-referenced dictionary entries on specific countries and regions, influential historical figures, laws that criminalized same-sex sexuality, various historical terms that have been used to refer to aspects of same-sex love, and contemporary events and legal decisions.